Drowning in a tsunami of online resources? Time to take stock and re-invent - Waller, B.; Pasanen, K. (British Journal of Sports Medicine, 2021)
Since lockdown and travel restrictions have been in force, there has been a tsunami of online courses, webinars, congresses and all other forms of learning platforms. The plethora of cancelled congresses led to a rush to put all the content online and deliver it through the computer. All great at saving time, but is trying to apply our old habits to the new norm useful? Let us be completely honest with ourselves, do we pay attention for 6 to 8 hours in an online congress? NO and NO (not that we ever did at a congress either, but there were better distractions often in the form of constructive debate with colleagues). Online congresses cannot provide the same opportunities to meet people during coffee breaks and social activities. Networking, meeting new people and conversations are often more valuable than congress sessions. Ask any student now forced to study at home, do they watch a 1½-hour lecture fully while taking endless notes or do they just turn their video off and possibly listen while completing another assignment? Everyone seems busier than ever and trying to push through the COVID-19 challenges, which might be the wrong approach. Let us stop, take a breath and see where we are headed. We need to reinvent the congress but retain the interactions that we all crave.